THE EFFECT OF OMEPRAZOL ON THE LIVER REGENERATION AND THE GASTRIC ACIDITY OF THE PARTIALLY HEPATECTOMIZED RATS - Musa AKOĞLU,; Vedat KIRIMLIOĞLU,; Uğur YILMAZ,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2020)
-